2023
DOI: 10.1590/1678-4324-2023220750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential Use of Oxy-Hydrogen Gas for the Treatment of Lactococcus garvieae Infected- Zebrafish in Hydrogen-Rich Water Aquarium

Abstract: This study aimed to evaluate the use of an oxy-hydrogen generator for preparing hydrogen-rich water (HRW) and studying its effects on the L. garvieae-affected zebrafish. 0, 10, 20, and 100% HRW were prepared to determine the effects of HRW on the mortality rate and gene expression levels of L. garvieae infected-zebrafish. After 48 hours of bacterial injection, the mortality rate of fish was 0, 0, 0, 66, 80, and 100% for the non-infected and non-HRW (G1), infected and 100% HRW (G5), non-infected and 100% HRW (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This study showed that no significant changes in the muscle layer thickness, mucosal thickness, villus width, and villus height occurred in largemouth bass treated with HRW. This is consistent with previous research [23]. This result indicates that HRW maintains the integrity and stability of the intestinal structure.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study showed that no significant changes in the muscle layer thickness, mucosal thickness, villus width, and villus height occurred in largemouth bass treated with HRW. This is consistent with previous research [23]. This result indicates that HRW maintains the integrity and stability of the intestinal structure.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, long−−term (180 days) HRW (1200 ppb) intervention can reduce the weight of rats [22]. Therefore, there was a dose-−response effect of hydrogen on animal growth [23]. In order to explore the appropriate concentration of hydrogen in largemouth bass, we set up two treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation